2019
DOI: 10.1128/mbio.01732-19
|View full text |Cite
|
Sign up to set email alerts
|

A Chaperone for the Stator Units of a Bacterial Flagellum

Abstract: The stator units of the flagellum supply power to the flagellar motor via ion transport across the cytoplasmic membrane and generate torque on the rotor for rotation. Flagellar motors across bacterial species have evolved adaptations that impact and enhance stator function to meet the demands of each species, including producing stator units using different fuel types or various stator units for different motility modalities. Campylobacter jejuni produces one of the most complex and powerful flagellar motors b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…This increased proton flow would presumably disrupt proton motive force homeostasis in the cell, perhaps due to electron leakage across the electron transport chain, as has been proposed by Flint et al, which could explain the observed growth inhibition (Flint et al, 2014). To begin to examine this hypothesis, we tested whether FlaGrab could inhibit the growth of motA or motB mutants, which have a "paralyzed" flagellar phenotype as they each lack a key element of the flagellar motor (Ribardo et al, 2019). We predicted that these mutants would be bound, but not cleared by FlaGrab.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This increased proton flow would presumably disrupt proton motive force homeostasis in the cell, perhaps due to electron leakage across the electron transport chain, as has been proposed by Flint et al, which could explain the observed growth inhibition (Flint et al, 2014). To begin to examine this hypothesis, we tested whether FlaGrab could inhibit the growth of motA or motB mutants, which have a "paralyzed" flagellar phenotype as they each lack a key element of the flagellar motor (Ribardo et al, 2019). We predicted that these mutants would be bound, but not cleared by FlaGrab.…”
Section: Discussionmentioning
confidence: 92%
“…This increased proton flow might in turn disrupt the electron transport chain (as proposed by Flint et al, 2014), which could prompt cells to respond by altering transcription of energy metabolism pathways. We predicted that if this were true, flagellar motility mutants, such as motA and motB, which do not express functional flagellar motors, would resist FlaGrab-induced clearing (Beeby et al, 2016;Ribardo et al, 2019). To test this, we generated insertional mutants in each of motA and motB in C. jejuni 11168 and confirmed that these mutants were non-motile ( Figure S2).…”
Section: Flagrab Binding To Flagellar Motor Mutants Mota and Motb Doementioning
confidence: 99%
“…The motors of E. coli and S. enterica have dynamic stators that continually associate and disassociate from the rotor in response to the external environment (Lele et al , 2013). The motors of some other species generate higher torque with wider, more highly‐occupied stator rings stabilized by periplasmic scaffolds and chaperones that directly interact with the stators to maintain their integrity (Beeby et al , 2016; Kaplan et al , 2019a; Ribardo et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Complexes containing MotB were isolated using antibodies and proteins identified by mass spectrometry. By applying a stringent criterion for interaction specificity (>2 6 -fold difference in protein amount between the anti-MotB antibody and IgG control), we identified six significant MotB interactions: PilO, PilN, PilM, a FlgX homolog that is a stator-unit chaperone in Campylobacter jejuni ( 21 ), a hypothetical protein, and MotB’s known interaction partner MotA ( Fig. 2 B and SI Appendix , Fig.…”
Section: Resultsmentioning
confidence: 99%